Inovasi Manajemen Kelulusan Teknik Otomotif Dapat Bekerja di DU/DI dan Mandiri dari SMK N 1 Girisubo - Sucahyani, Veni (Media Manajemen Pendidikan, 2024)
The aim of the research is to analyze the management functions related to management elements including planning, organizing, implementing, supervising, management innovations for automotive engineering graduates can work in DU/DI and independently, in addition to analyzing supporting and inhibiting factors and their solutions in automotive engineering graduation management innovations can work in DU/DI and independently from SMK N 1 Girisubo. This type of research uses qualitative research, research subjects are school principals, vice curricula, heads of automotive engineering vocational schools, and automotive engineering vocational teachers. Sources of data were obtained from informants, activities and documentation, the techniques used were observation, interviews, documentation, for data validity using source triangulation, technical triangulation, and time triangulation, data analysis in this study used data collection, data reduction, data presentation, then verification, from the results of innovation management research, automotive engineering graduates can work in DU/DI and independently from SMK N 1 Girisubo, it is said that it has been running well in accordance with management functions related to elements of management, this has met the standards set by PT DAIHATSU. The management element is a supporting factor in the management innovation of automotive engineering graduates being able to work in DU/DI and independently from SMK N 1 Girisubo, there are always obstacles to overcome these obstacles carried out by the school so that these obstacles do not affect management innovation.